2017
DOI: 10.1186/s12910-017-0192-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-tests for influenza: an empirical ethics investigation

Abstract: BackgroundIn this article we aim to assess the ethical desirability of self-test diagnostic kits for influenza, focusing in particular on the potential benefits and challenges posed by a new, mobile phone-based tool currently being developed by i-sense, an interdisciplinary research collaboration based (primarily) at University College London and funded by the Engineering and Physical Sciences Research Council.MethodsOur study adopts an empirical ethics approach, supplementing an initial review into the ethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Comprehensive legislation like the General Data Protection Regulation in the EU has started to tackle this issue, but more tailor-made methods, such as the voluntary privacy code for mHealth apps [ 81 ], are needed. Recent ethics studies [ 82 ] also found that consumers need to consider and agree to all facets of the use of their results.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive legislation like the General Data Protection Regulation in the EU has started to tackle this issue, but more tailor-made methods, such as the voluntary privacy code for mHealth apps [ 81 ], are needed. Recent ethics studies [ 82 ] also found that consumers need to consider and agree to all facets of the use of their results.…”
Section: Discussionmentioning
confidence: 99%
“…Broad regulations such as the EU’s General Data Protection Regulation (GDPR) are beginning to address this, but more tailored approaches like the voluntary code of conduct on privacy for mHealth apps77 are needed. Moreover, recent ethics studies78 have highlighted the need for users to understand and consent to all aspects of how their data will be used.…”
Section: Data Connectivity To Health Systemsmentioning
confidence: 99%
“…The latest ethical studies have stressed the need for people to understand and consent to all aspects of how their personal data will be utilized ( Rumbold et al, 2017 ). Integrated platforms to share data, standardize security, organize collected data, and improve mHealth app connectivity and services are presented in the developmental stage ( Chen et al, 2012 ).…”
Section: Public Health Surveillance and Mobile-healthmentioning
confidence: 99%